Low-cost, LoRa GNSS tracker for wildlife monitoring - Adam F. Parlin; Ned A. Horning; Jason P. Alstad; Bradley J. Cosentino; James P. Gibbs (HardwareX, 2025)
The advent of GNSS tracking has allowed researchers to obtain detailed information on animal movement, which informs basic natural history and conservation management decisions. However, many devices are tailored to specific taxa thus limiting broader applicability. We present an open-source LoRaWAN (long range wide area network) GNSS (Global Navigation Satellite System) tracker, and an alternative commercial-off-the-shelf (COTS) development board global positioning system (GPS) tracker, a subset of the GNSS system. The COTS development board tracker provides a pathway for designing and implementing a general purpose LoRaWAN tracking unit, while the advantages of the Wildlife Movement Institute (WMI) tracker permit specific animal tracking and additional information to be collected, such as battery voltage, estimated precision error, and received signal strength intensity. Both units have documentation for setting up a LoRa application and network server and can be easily programmed using the Arduino Integrated Development Environment. To test the utility of these trackers in a LoRa data transmission application, we pilot tested the units on Eastern gray squirrels in Syracuse, New York, USA. Our trackers highlight the capability for customizable, open-source tracking technology that can be tailored to a suite of study organisms allowing researchers to design, develop, and deploy low-cost, specialized wildlife tracking equipment.